(untitled) (Training and Practice : Journal of Educational Sciences, 2015)
These days stress is the unfortunate concomitant of school life, concerning both teachers and students, and therefore making the education process more complicated. Stress effects and their consequences such as physical and mental strain and students’ behavioral problems are serious stress factors for the participants of the educational system. That is the reason why it is suggested to use such a relaxing method which helps relieving them of their stress and problems. The method presented in the lecture could quickly and easily be fitted into the everyday activities of a school class. In addition, this method doesn’t only help dealing with stress but plays an important role in community development and may help facilitating the learning process. The author applied the method (Autogenic Training and Progressive Relaxation) in four school classes in order to assist students’ mental health. The classes involved have been followed up for several years. In the light of the results, the author found the method applicable in elementary classes and with certain changes in high school classes as well.